POLITICAL REPRESSIONS AGAINST GERMAN COLONISTS IN THE BORDER AREAS OF THE ZHYTOMYR REGION IN 1937-1938. - Суліменко, Олександр (SWorldJournal, 2024)
The purpose of the article is to study the period of mass political repressions in 1937-1938 against German colonists who lived compactly in the border areas of the Zhytomyr region. The methodological basis of the study is a systematic approach to the stu